Spirit of Bureaucratic Change of Decision Makers in Banyumas District Facing Challenges in the VUCA Era - Shadu Satwika Wijaya; Slamet Rosyadi (Jurnal Public Policy, 2023)
Decentralization requires the bureaucracy to be able to solve various problems faced by the community at the local level. Meanwhile, the context of social change in society is directly proportional to the complexity of opportunities. The greater the complexity of the opportunity, the greater the uncertainty. The VUCA Era created uncertainty in human civilization, including public administration. Public administration must ensure how far the uncertainties in the VUCA Era can be anticipated in efforts to organize public administration, particularly in the decision-making process. For this reason, this article aims to identify the spirit of change in decision-making bureaucrats in Banyumas Regency to face the VUCA Era. The method used is a descriptive quantitative approach. Data was collected using a survey method for decision-making bureaucrats within government agencies in Banyumas Regency. The results of the study show that the level of spirit of change in decision-maker bureaucrats in Banyumas Regency in facing challenges in the VUCA era is at a moderate level. This indicates that decision-making bureaucrats still need support and encouragement in facing challenges in the VUCA era, especially adaptability and sustainable positive change.